Saberes e fazeres no período colonial em Goiás: a construção do conhecimento a partir da aula oficina - Lima, Glauce Christiny Goulart Souza (2024)
This dissertation aims to analyze the importance of the workshop-class as a process of construction of historical knowledge about pottery production in the colonial period in Goiás. From the year 2000, archaeological excavations were carried out in the historic center of the city of Goiás, where ceramic objects left by the colonial society of that place were found, which were cataloged by the Archaeology Center of the State University of Goiás, coordinated by Professor Gislaine Valério de Lima. From this work carried out, from the comparison with dissertations, theses, articles, books, the historiographical production of the PPGH-UFG and the methodology of Isabel Barca's workshop class, a field activity was planned and executed with students of the second year of High School of the State College of the Military Police of Goiás, Américo Antunes Unit, in the municipality of São Luís de Montes Belos, with the objective of building students' knowledge about the daily practices and knowledge related to the production of ceramic objects in the colonial world